Challenging secular establishment: Student movements in Egypt and Turkey in the 1970s - (:unkn) unknown (Duke University Press, 2014)
Student movements in the twentieth century Middle East have received less attention than many other topics in the study of the region's cultural and political history. Yet the rapidly changing demographic composition of the region since the 1960s have made young people and youth activism a significant parameter in Middle Eastern politics, highlighted by the Arab Spring that began in late 2010. Student movements in Turkey and Egypt gained momentum in the 1960, and in the 1970s Islamic discourse became increasingly popular among young activists. These youth movements operated through flexible structures, allowing them to challenge the state authority and secular statecraft. This essay explores three of the leading religious and nationalist student movements in Turkey and Egypt in the 1970s.